Pharmacists' active interventions as a means to identify medication misadventure in pediatrics - Ramadaniati, H.; Lee, Ya Ping; Hughes, J. (2014)
PURPOSE: This study retrospectively analyzed the documentation of pharmacists’ active interventions in order to (i) determine the reliability of researchers’ and independent panelists’ judgement regarding identification, classification and outcome severity of medication misadventure detected through pharmacists’ interventions, and (ii) determine the pattern and the severity of medication error METHODS: The researchers and three independent panelists assessed randomly selected pharmacists’ active interventions. The reviewers identified the presence of medication misadventures and classified them by type (adverse drug events/ADEs, adverse drug reactions/ADRs, medication errors/MEs). Medication errors were then classified by type and rated for their severity using the National Coordinating Council on Medication Error Reporting and Prevention index. Inter-rater reliabilities were calculated using the kappa statistics ( j ) statistics. As the consensus cannot be reached, the researchers’ assessment was used as the final rating. RESULTS: Agreement between all reviewers regarding the presence of medication misadventure was “fair ( j = 0.302) and “slight” ( j = 0.115) for the type of the misadventure. “Moderate” agreement ( j = 0.477) was noted when classifying the type of medication error, but “slight” for the error severity ( j = 0.044). Based on the researchers’ consensus, approximately three quarters of the selected samples (33/43) of pharmacists’ active interventions addressed medication misadventures, with around 91% of the misadventure involving MEs and the remaining ADRs. Over- all the most common type of medication errors were related to inappropriate doses. Approximately 39% of medication errors were corrected before they could harm the patient, whilst more than 60% of the non-intercepted errors resulted in either additional monitoring or temporary patient harm. CONCLUSION: This study showed the clear role clinical pharmacists play in reducing medication misadventure in the pediatric setting, particularly through identifying and resolving medication errors.